Factors associated with good self-rated health of non-disabled elderly living alone in Japan: a cross-sectional study - Saito Masahisa; Kono Rei; Shibutani Takahiro; Tanimoto Yoshimi; Watanabe Misuzu; Sun Wei; Usuda Kan; Kono Koichi (BMC, 2007)
Abstract Background Self-rated health (SRH) is reported as a reliable predictor of disability and mortality in the aged population and has been studied worldwide to enhance the quality of life of the elderly. Nowadays, the elderly living alone, a particular population at great risk of suffering physical and mental health problems, is increasing rapidly in Japan and could potentially make up the majority of the aged population. However, few data are available pertaining to SRH of this population. Given the fact that sufficient healthcare is provided to the disabled elderly whereas there is little support for non-disabled elderly, we designed this population-based survey to investigate SRH of non-disabled elderly living alone and to identify the factors associated with good SRH with the purpose of aiding health promotion for the elderly. Methods A cross-sectional study was conducted in a metropolitan suburb in Japan. Questionnaires pertaining to SRH and physical conditions, lifestyle factors, psychological status, and social activities, were distributed in October 2005 to individuals aged ≥ 65 years and living alone. Response rate was 75.1%. Among these respondents, a total of 600 male and 2587 female respondents were identified as non-disabled elderly living alone and became our subjects. Multivariate logistic regression was used to identify the factors associated with good SRH and sex-specific effect was tested by stepwise logistic regression. Results Good SRH was reported by 69.8% of men and 73.8% of women. Multivariate logistic regression analysis showed that good SRH correlated with, in odds ratio sequence, "can go out alone to distant places", no depression, no weight loss, absence of self-rated chronic disease, good chewing ability, and good visual ability in men; whereas with "can go out alone to distant places", absence of self-rated chronic disease, no weight loss, no depression, no risk of falling, independent IADL, good chewing ability, good visual ability, and social integration (attend) in women. Conclusion For the non-disabled elderly living alone, sex-appropriate support should be considered by health promotion systems from the view point of SRH. Overall, the ability to go out alone to distant places is crucial to SRH of both men and women.